STRATEGI GURU DALAM MENINGKATKAN MINAT BACA SISWA DI SD SWASTA ANNYSA - Rahmatun Nisa; Muhammad Chaidir; Bintang Ridzky Dwi Putra; Abdul Fattah Nasution (MERDEKA : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explore the strategies implemented by teachers to increase students’ reading interest at SD Swasta Annysa. Reading interest among elementary students in Indonesia remains relatively low, influenced by the widespread use of digital technology and limited family support for reading habits at home. The study applied a qualitative approach with a case study method, involving in-depth interviews with teachers and documentation of literacy activities at school. The findings revealed that teachers face various challenges, including students’ preference for gadgets over books and the lack of parental involvement in fostering reading habits at home. To address these issues, teachers introduced strategies such as daily 15-minute reading sessions before lessons and encouraging students to retell what they have read in front of the class. These methods not only build reading routines but also enhance students' comprehension and verbal communication skills. This study highlights the crucial role of collaboration among schools, teachers, parents, and the wider community in cultivating a sustainable and effective reading culture. The results of this research are expected to serve as a practical reference for educators in developing literacy strategies that are contextual and aligned with the needs of elementary students in the digital era.